Modeling for computer graphics study in terms of fundamentalization of information science - Sultangaliyeva L.4, Suleimenova G.5, Baidrakhmanova G.A.1, Issabayeva D.N.2, Rakhimzhanova L.B.3, (Opción, 2019)
The research objective consists of consideration and applicationof a technique for teaching computer graphics by means ofinformation model creation via the method of computer graphics studyby means of information models. The results of the pedagogicalexperiment prove the reliability and effectiveness of the techniqueconnected with computer information modeling in the process ofcomputer graphics teaching. In conclusion, the fundamentalization ofeducation, the course of information science particularly must beconstructed from a phenomenon of information processes to methodsof their study by means of information models, using computer as atool to control the information processes.